1996
DOI: 10.2337/diacare.19.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria in Patients With NIDDM: An Overview

Abstract: We have come a long way in our understanding of the epidemiology, pathophysiology, and clinical significance of albuminuria in patients with NIDDM. However, substantial gaps remain to be defined. NIDDM nephropathy is a serious and increasingly burdensome disease for both the diabetic individual and the society at large. Onset of microalbuminuria, an early but common manifestation of NIDDM nephropathy, marks an ominous turn for the NIDDM patient, in whom its development forecasts a grave cardiovascular outcome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 45 publications
2
54
0
2
Order By: Relevance
“…In favour of this view, are the observations indicating that tighter blood glucose control reduces the incidence and progression of cardiovascular complications and of diabetic nephropathy. 7,23,24 In addition, subsequent development of hypertension and/or worsening or existing hypertension elevation of the BP, and development of a state of salt sensitivity, may also play a role in the development of microalbuminuria. 25 Because of the well-known male and female pattern of body fat distribution, 16 we separately evaluated the relationships between abdominal fat and albuminuria in males and females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In favour of this view, are the observations indicating that tighter blood glucose control reduces the incidence and progression of cardiovascular complications and of diabetic nephropathy. 7,23,24 In addition, subsequent development of hypertension and/or worsening or existing hypertension elevation of the BP, and development of a state of salt sensitivity, may also play a role in the development of microalbuminuria. 25 Because of the well-known male and female pattern of body fat distribution, 16 we separately evaluated the relationships between abdominal fat and albuminuria in males and females.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] Moreover, it has been reported that even in non-diabetic subjects the presence of microalbuminuria may be associated with increased atherosclerotic risk factors and cardiovascular morbidity and mortality. [8][9][10][11] However, what determines microalbuminuria in normotensive nondiabetic subjects is unknown.…”
Section: Journal Of Human Hypertension (2001) 15 407-412mentioning
confidence: 99%
“…Urine samples from healthy Saudi subjects without any history of renal disease, hypertension or diabetes mellitus were free of glucose, had normal pH values and NAG [17] , AAP [18] , microalbuminuria [19] and total protein values ( Table 1). No significant differences were found between males and females, data was then pooled for the whole group.…”
Section: Normal Subjectsmentioning
confidence: 99%
“…An ACR of 2.0 -2.5 mg/mmol to 20-35 mg/mmol corresponds to albumin excretion of 20 -200 µg/min or 30 -300 mg/day. 27,28,29 In this study control subjects mean±2SD of urinary albumin creatinine ratio (ACR) was 2.77 mg/mmol. ACR 2.77mg/mmol was taken as a cut-off value.…”
Section: Introductionmentioning
confidence: 99%